Detection of Anomalous Cervical Internal Carotid Artery Branches by Colour Duplex Ultrasound. (June 2017) - Busch, K.; Chandra, R.; Buckenham, T.; Kiat, H.
Abstract : Objectives: Conventional anatomical descriptions of the cervical internal carotid artery (ICA) report that no branches arise from this segment. However reports of ICA branches exist. The study aim was to determine the prevalence of anomalous branches of the ICA using colour duplex ultrasound (CDU). Methods: Four hundred consecutive patients (800 carotid vessels) referred to a tertiary hospital vascular laboratory for investigation of carotid disease were included. A clear differentiation of a low resistive ICA and a high resistive external carotid artery (ECA) waveform was required. CDU was performed on a Philips IU22 ultrasound system with a 9–3 MHz linear array transducer employing a standard carotid imaging protocol. The origin of each ICA branch was identified using B-mode and CDU. Anatomical orientation of ICA branches and distance from bifurcation was recorded and spectral CDU analysis was performed. Results: Twenty ICA branches, tracking cephaladly, were detected in 16 patients (4%), or 2.5% (20/800) vessels. The median age was 73 years; 50% were female and 50% male. All patients demonstrated a single branch [unilateral anomaly ( n  = 12 patients), bilateral anomaly ( n  = 4) patients]. Eighty-five percent arose from the posterior wall of the ICA. The median distance from ICA bifurcation was 4 mm (range 0–18 mm). ICA branch diameters ranged from 1.2 mm to 2.4 mm (median 1.4 mm, mean 1.6 mm). Eighty percent of ICA branches had less than 50% stenosis. Spectral analysis revealed high resistive waveforms in all branches. Conclusions: Branches from the ICA exist and can be characterised with CDU. Prevalence in a tertiary hospital referral cohort is 4%. Given their potential clinical implications, standard carotid imaging protocols should consider routine assessment and reporting of ICA branches.